Multicultural relations on campus : a personal growth approach - Parker, Woodrow M.; Archer, James, Jr.; Scott, James E., Ph. D. (New York : Routledge, 2009)
First published in 1992. Routledge is an imprint of Taylor & Francis, an informa company.
Sender
English
Includes bibliographical references and index.
Description based on print version record.
First published 1992 by Accelerated Development.
Keywords: Multicultural education -- United States; Cross-cultural orientation -- United States; Universities and colleges -- United States; Activity programs in education -- United States